Arthroscopic Suture Fixation of Tibial Eminence Fracture - Gehron P. Treme MD; Dustin L. Richter MD (SAGE Publishing, 2021)
Background: Tibial eminence fractures account for up to 5% of knee injuries with an effusion in the pediatric population. Displaced fractures require reduction and operative fixation via arthroscopic or open techniques. Indications: Arthroscopic suture fixation and screw fixation are 2 of the most commonly described techniques for tibial eminence fracture treatment. We describe our preferred technique of arthroscopic suture fixation given the versatility of this technique and decreased risks of hardware irritation or impingement, need for reoperation, and minimal risk of physeal damage. Technique Description: The arthroscopic suture fixation technique uses a standard anteromedial and anterolateral portal. After the fracture bed and hematoma are debrided and any interposing structures (ie, meniscus) are removed from the fracture site, 2 nonabsorbable sutures are passed through the substance of the anterior cruciate ligament (ACL). Using an ACL guide, 2 separate transtibial tunnels are drilled with a bone bridge in between-one at the anterolateral aspect of the fracture base and one at the anteromedial aspect. One limb from each suture is pulled out from each of the bone tunnels. The fragment is then reduced, and the sutures are tensioned and fixated using knotless suture anchors. Results: Overall prognosis following tibial eminence fracture fixation is favorable with more than 80% of patients returning to prior level of activity. Arthrofibrosis may occur in up to 25% of patients. Although some residual laxity may remain, there is a high return to sport and no difference in rate of subsequent ACL injury or surgery compared with a match cohort of pediatric ACL reconstructions. Discussion: Arthroscopic suture fixation of displaced tibial eminence fractures is a reliable technique with high return to sport and low risk of reoperation. Arthrofibrosis is common; thus, early, controlled knee range of motion following surgery is critical.